Implementation of the Smoke-Free and Limited Smoking Area Policy in Jeneponto Regency - Sakawati, Herlina; Hamrah, Hamrah; Halim, Didin (Universitas Negeri Makassar, 2023)
This research aims to determine the implementation of smoke-free and limited smoking area policies. This research includes descriptive qualitative research with data collection techniques through observation, interviews and documentation. The data analysis techniques used are data condensation, data presentation, and drawing conclusions. The results of this research indicate that the implementation of smoke-free and limited smoking area policies in Jeneponto Regency. Judging from the four variables, namely, communication, resources, disposition and bureaucratic structure in implementing the smoke-free and limited-smoking area policy, it is still not good and still needs to be improved from the indicators that the communication carried out is still unclear, budget resources and facilities are still inadequate. , the implementer's disposition is still not firm enough in implementing the policy and the organizational structure is still unclear and needs to be evaluated so that the implementation of the smoke-free and limited area policy runs well in accordance with the policy objectives. The suggestions for this research are to disseminate information more directly and clearly, increase supervision and apply strict sanctions, comply with and implement the smoke-free and limited smoking area policy.